Anxiety and depression among infertile couple in Malaysia/ Fatimah Sham ... [et al.] - Sham, Fatimah (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Infertility is a life crisis affecting patients from all over the world. The risk of anxiety and depression is high for infertile patients which affects the stages and outcome of the treatment. The need to understand the Asian perspective related to the stigma of infertility stigma and psychological distress may be a source of hindrance in seeking professional intervention. This cross-sectional study included 170 infertile patients (85 couples) in a referral fertility center in a Malaysian Government Hospital. Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI) were administrated to all participants. The level of anxiety among these couples was moderate (median=24.5, IQR=8) as well as the result for the level of depression was reported at the moderate level (median=26, IQR=10). The wives were significantly more likely to report high in depression (x2: 9.70; p-value: 0.02). The respondents' level of depression was found strongly and positively related to their age (rs: 0.58; p-value: 0.01). While both the anxiety (rs = 0.61, p-value =0.01) and depression (rs = 0.15, p-value =0.04) were positively associated with duration of infertility. It is important for the health care providers especially the nurses to play an active role in the detection and identification of this psychological distress in order to provide assistance and obtaining appropriate help especially dealing with the clients’ emotional needs.